Biodigester rapid analysis and design system (B-RADeS): A candidate attainable region-based simulator for the synthesis of biogas reactor structures. (4th January 2020) - Abunde Neba, F.; Asiedu, Nana Y.; Addo, Ahmad; Morken, John; Østerhus, Stein W.; Seidu, Razak
Highlights: A model-based methodology for synthesis of digester networks is developed. Only experimental measurements of biogas yield are required for synthesis. The concept of attainable regions is used to couple biokinetics and macroeconomics. A software is developed to implement the framework and tested on three substrates. The choice of macroeconomic parameter influences the nature of digester structure. Abstract: Anaerobic digesters are seldom designed based on process kinetics, but rather on a combination of hydraulic and organic loading, which may limit operational performance. This study focuses on the incorporation of process kinetics in the design of anaerobic digesters, within the attainable region conceptual framework. Candidate attainable regions for anaerobic digesters are identified using the software environment Biodigester Rapid Analysis and Design System (B-RADeS), which couples, biodegradation kinetics as well as economic parameters for the synthesis of biodigester structures. By considering swine, palm oil and pharmaceutical wastewaters, payback periods of 0.5, 1 & 2 years, and substrate, kinetic model and/or economic parameters, a promising digester structure (and associated hydraulic retention times) is synthesized, consisting of a CSTR followed by PFR (15 days), CSTR (4.8 hours) and a PFR with bypass of feed (3 days). The framework offers great promise for widespread practical application.